A randomized control trial of Expand Your Horizon: An intervention for women with weight bias internalization. (March 2022) - Davies, Alexandria E.; Burnette, C. Blair; Ravyts, Scott G.; Mazzeo, Suzanne E.
Highlights: Compared a body gratitude intervention to an active control to lower weight bias. Functionality appreciation, self-compassion, and healthcare stress were also tested. Both conditions demonstrated improvements on study variables. The effects over time were stronger for intervention participants. Body gratitude journaling has promise in improving body-related esteem. Abstract: Weight bias internalization (WBI) is associated with a myriad of negative health outcomes, but there are few effective treatments that address this concern. This randomized controlled trial examined the preliminary effectiveness of a previously developed body gratitude journaling intervention (i.e., Expand Your Horizon ) compared with an active control writing condition (i.e., expressive writing) in emerging adult women with WBI. Participants ( N = 135) completed baseline measures and were then randomized to either Expand Your Horizon ( n = 72) or the active control condition ( n = 63). Participants in both conditions completed three writing tasks over one week. Assessments occurred at baseline, post-test, and follow-up (one-week). Participants in both conditions experienced improvements in WBI, functionality appreciation, and self-compassion at follow-up, though improvements were greater in the Expand Your Horizon condition. Further, participants in the Expand Your Horizon had greater improvement in healthcare stress at follow-up. In sum, Expand Your Horizon appeared accessible and demonstrated preliminary effectiveness in a sample of emerging adult women with WBI. Avenues for future research include evaluating this intervention in more diverse populations with a longer follow-up.